Nanostructured CeO2 coating for high temperature oxidation protection. (2nd June 2016) - Ghosh, D.; Roy, H.; Das, S.; Mitra, S. K.
Abstract : This paper investigates the influence of nanostructured ceria (CeO2 ) coating on high temperature oxidation behaviour of 2·25 Cr-1 Mo steel. The isothermal corrosion study of the micrometre size and nanostructured CeO2 coated specimens was conducted in air oxidation environment at 973 K for 8 h. The corrosion rate and reaction kinetics were studied, and the post-corroded scales were characterised by field emission scanning electron microscopy and X-ray diffraction. The results clearly indicate that the nanostructured CeO2 coated specimen improves the oxidation resistance in comparison to the micrometre size CeO2 coated specimen. The improvement of oxidation resistance in the case of nanostructured CeO2 coating can be attributed to the formation of semimolten zone, which consists of nanostructured CeO2 particle. On the other hand, in the absence of semimolten nanostructured zone, the micrometre size CeO2 coated specimen shows higher corrosion rate in comparison to the nanostructured CeO2 powder coated specimen.